The VIX, the variance premium and stock market volatility - Geert Bekaert; Marie Hoerova (European Central Bank (ECB), 2014)
We decompose the squared VIX index, derived from US S&P500; options prices, into the conditional variance of stock returns and the equity variance premium. We evaluate a plethora of state-of-the-art volatility forecasting models to produce an accurate measure of the conditional variance. We then examine the predictive power of the VIX and its two components for stock market returns, economic activity and financial instability. The variance premium predicts stock returns while the conditional stock market variance predicts economic activity and has a relatively higher predictive power for financial instability than does the variance premium.
Keywords: C22; C52; G12; E32; 330; economic uncertainty; financial instability; option implied volatility; realized volatility; risk aversion; risk-return trade-off; stock return predictability; variance risk premium; VIX